Switching loss and temperature analysis of MPWM controller for solar PV inverter - Panneerselvam, Sivaraj; Kandasamy, Karunanithi; Sivakumar, S.; Prasanna, N. Vignesh; Hushein, R. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Despite the fact that temperature affects how much power is produced by solar panels, a temperature that exceeds a certain threshold results in a reduction in output. Additionally, there are losses when switching is controlled in inverters using different control approaches like pulse width modulation (PWM), sinusoidal pulse width modulation (SPWM), and multiple pulse width modulation (MPWM). The type of control method and temperature have an impact on these losses. Here, the MPWM approach is used to analyze it at various temperatures. A metal-oxide-semiconductor field-effect transistor or MOSFET-based and an insulated gate bipolar transistor (IGBT)-based inverter are also planned. Their switching losses at various temperatures are contrasted. For a range of temperature values, the IGBT-equipped inverter is discovered to be a low-loss inverter. Compared to an IGBT inverter, the MOSFET inverter has a comparatively higher loss.